FRI0289 Multicenter Registry on Inflammatory Myopathies in Madrid (REMICAM): Mortality Analysis. (15th July 2016) - Nuño, L.; García, M.J.; Joven, B.; Maldonado, V.; Llorente, I.; Barbadillo, C.; García de la Peña, P.; Ruiz, L.; Moruno, H.; Cobo, T.; Almodovar, R.; Lojo, L.; et al.
Abstract : Background: Classically the prognosis of idiopathic inflammatory myopathies (IIM) has improved in recent decades, but can still be poor in certain subgroups or in the presence of some clinical factors. Objectives: To analyze survival, causes of death and poor prognosis factors in a cohort of patients diagnosed with IIM. Methods: A multicenter retrospective study from REMICAM 1 myositis study group was performed. All patients were diagnosed with IIM according to Bohan and Peter 2 criteria and were classified into 5 different clinical subgroups: primary dermatomyositis (DM), primary polymyositis (PM), juvenile dermatomyositis (JuvM), cancer associated myositis (CAM) and overlap myositis (OM). Results: 478 IIM cases were included. 74% of the cases were women, with an age at diagnosis of 43.7±22.6 ys. and a mean follow-up of 9.7±8.3 ys. During the follow-up period there were a total of 114 deaths (24%), the main causes were infections (24%), cancer (24%), and cardiovascular events (22%). Factors associated with poor prognosis were CAM (HR 15.4) and OM subgroups (HR 4.55), older age at diagnosis (HR 1.05), shorter time of disease (HR 1.30), serious infections (HR 4.57), cancer (HR 3.07), systemic symptoms (HR 1.64), heart (HR 2.52) and haematological manifestations (HR 1.53), ESR/CRP elevation at baseline (HR 3.05) and chronic renal failure (HR 2.41). The clinical characteristics that showed a protective effect were arthralgia (HR 0.68), typical skin lesions (HR 0.62), drug use (HR 0.53) and female sex (HR 0.5). In multivariate analysis the independent variables associated with mortality were CAM (HR 8.83) and OM (HR 5.17) subgroups, severe infections (HR 3.42), older age at diagnosis (HR 1.03), shorter course of the disease (HR 1.34), thrombocytopenia (HR 2.93) and elevated ESR/CRP (HR 2.47). Conclusions: In our REMICAM registry on inflammatory myopathies 24% of patients died, mainly due to infections, cancer and cardiovascular events. The independent predictors of mortality were belonging to the subgroups of paraneoplastic myopathies or overlap syndrome, the presence of severe infections, thrombocytopenia, elevated ESR/CRP at baseline, shorter course of the disease and older age at onset. References: REMICAM: Registry on inflammatory myopathies in Madrid Bohan A, Peter JB. N Engl J Med 1975 Feb 13;292(7):344–7. Disclosure of Interest: L. Nuño Grant/research support from: SORCOM-MSD grant for myositis study, M. J. García: None declared, B. Joven: None declared, V. Maldonado: None declared, I. Llorente: None declared, C. Barbadillo: None declared, P. García de la Peña: None declared, L. Ruiz: None declared, H. Moruno: None declared, T. Cobo: None declared, R. Almodovar: None declared, L. Lojo: None declared, F. J. Lόpez Longo: None declared